Percepciones de la utilidad de las aulas virtuales por parte de los estudiantes de la carrera de Pedagogía de las Ciencias Experimentales: Informática durante el periodo de educación no presencial de emergencia por la pandemia del covid-19. - Guapulema Vilema, Narciza Paulina (2023)
Due to the health emergency caused by the COVID-19 pandemic that swept the world, the Ecuadorian educational system faced this pandemic through emergency non-face-toface education supported by Information and Communication Technologies (TIC). Thus, the National University of Chimborazo saw the need for the use of virtual classrooms through Learning Management Systems, where teachers could share content. In this sense, the objective of this research work was to know the perception of the students of the Pedagogy of Experimental Sciences: Informatics career on the usefulness of virtual classrooms during the period of non-face-to-face emergency education due to the COVID pandemic. -19. This research was developed in the 2021-2S academic period and had a quantitative approach with a descriptive scope and a cross-sectional non-experimental design because the data was collected at a single moment, in addition, a sample of 116 students was worked on. The information was collected through the adaptation of an already published questionnaire. Among the main results obtained in the seven dimensions analyzed, it was observed that more than 70% of the students had a positive perspective on the use of Virtual Classrooms for their learning processes. This allowed them to access learning content quickly no matter where they were, so they could reinforce the knowledge acquired in class as well as develop autonomous and collaborative learning.